Softening of elastic moduli of amorphous semiconductors - Kelires, Pantelis C.; Mathioudakis, Christos (My University, 2000)
We study the rigidity problem of amorphous semiconductors using Monte Carlo (MC) simulations and empirical potentials. We find that networks of tetrahedral a-C, a-Si, and a-Ge consistently have smaller elastic moduli than their crystalline counterparts. The reduction of rigidity seems to be associated with the reduced density and the random orientation of sp3 hybrids in the fully tetrahedral amorphous networks and, in addition, with the presence of sp2 sites in tetrahedral a-C.
Keywords: Semiconductors